The role of beta-lactamase in low-level cephalosporin-resistant serratia marcescens - Herra, Celine M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2002)
In enterobacteria, high-level cephalosporin resistance is commonly mediated by constitutive over-production or derepression of chromosomal AmpC β-lactamase. This derepression is frequently associated with mutations in the ampD regulatory gene but altered AmpC expression may also result from mutation in the ampR regulatory gene or in the structural ampC gene.
Keywords: Clinical Microbiology, Ph.D.; Ph.D. Trinity College Dublin